Polymeric nanoparticles – a novel solution for delivery of antimicrobial agents - Grzegorz Michalak; Katarzyna Głuszek; Ewelina Piktel; Piotr Deptuła; Irena Puszkarz; Katarzyna Niemirowicz; Robert Bucki (Studia Medyczne, 2016)
The increased prevalence of antibiotic-resistant pathogens requires additional efforts to develop new antimicrobial agents and alternative methods to prevent and treat infections. In response to this challenge, a variety of nanotechnology-based tools are currently being designed and thoroughly investigated. To date, a considerable number of studies have reported increased activity of antibiotic-conjugated polymeric nanoparticles against bacteria and fungi associated with various infections, including those caused by drug-resistant pathogens. Importantly, high biocompatibility of these structures coupled with enhanced biological activity and improved pharmacokinetic properties supports the potential of these nanosystems as new tools to treat infections. In this review, we summarize the synthesis of polymer-based nanoparticles and describe their mechanism of action. We also highlight the recent advances in the application of antibiotic-conjugated polymeric nanoparticles as novel antimicrobial agents.